Scissor Bite in Growing Patients: Case Report Treated with Clear Aligners - Teresa Pinho; Sara Gonçalves; Duarte Rocha; Maria Luís Martins (Children, 2023)
Scissor bite (SB.) is a rare malocclusion that is challenging to diagnose and is often associated with a retrognathic mandible and a series of functional and structural abnormalities that negatively affect the patient. This article intends to analyze the treatment approaches applied to growing patients younger than 16 years old, comparing the conventional appliances described in the literature and a clinical case treated with clear aligners with mandibular advancement (MA.). SB is primarily related to skeletal Class I and II, according to Angle classification. In the various cases analyzed, it can also be mentioned as a significant number of cases with SB of dental origin (seven of dental and four of skeletal) in young patients. In children and adolescents who still have growth potential, the therapeutic possibilities are numerous. A comprehensive literature search was manually performed from 2002 until January 2023, in PubMed and BVS databases with the following conjugated keywords: “scissor bite OR brodie bite” AND “malocclusion” AND “treatment OR correction OR therapeutics”. The present case report on a young patient demonstrated the efficiency of the clear aligners with MA to correct an SB, associated with several functional and structural anomalies such as Class II division 1 with an increased overjet and overbite as well as a severe curve of Spee in a hypodivergent biotype.